2008
DOI: 10.1007/s11199-008-9517-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Self-Esteem in American and British College Women: Relations with Self-Objectification and Eating Problems

Abstract: The present study extended Objectification Theory (Fredrickson and Roberts, Psychol Women Q 21:173-206, 1997) to test the role of sexual self-esteem in models of disordered eating. Measures of self-objectification, sexual well-being, and disordered eating were completed by American (N=104) and British (N=111) college women. In Study 1, higher self-objectification was associated with lower sexual self-esteem, which, in turn, mediated the relationship between self-objectification and disordered eating in Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 80 publications
3
38
1
Order By: Relevance
“…Data from the US, Australia, and Britain support many of the theoretical propositions outlined in Objectification theory. Researchers have found that adolescent girls and young women who report higher levels of body surveillance also report greater general shame, body shame, appearance anxiety, body dissatisfaction, depressive symptoms, and disordered eating patterns as well as decreased body esteem, peak motivational states, and sexual functioning (Calogero 2004;Calogero and Thompson 2009;Fredrickson et al 1998;Quinn et al 2006;Steer and Tiggemann 2008;McKinley 1998;Moradi et al 2005;Tiggemann and Kuring 2004;Tiggemann and Slater 2001;Tylka 2004). It is also noteworthy that in a sample of American participants experimentally induced to focus on their bodies, women and not men, continued to have body-related thoughts after the study was presumably over (Quinn et al 2006).…”
Section: Objectification Theory and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the US, Australia, and Britain support many of the theoretical propositions outlined in Objectification theory. Researchers have found that adolescent girls and young women who report higher levels of body surveillance also report greater general shame, body shame, appearance anxiety, body dissatisfaction, depressive symptoms, and disordered eating patterns as well as decreased body esteem, peak motivational states, and sexual functioning (Calogero 2004;Calogero and Thompson 2009;Fredrickson et al 1998;Quinn et al 2006;Steer and Tiggemann 2008;McKinley 1998;Moradi et al 2005;Tiggemann and Kuring 2004;Tiggemann and Slater 2001;Tylka 2004). It is also noteworthy that in a sample of American participants experimentally induced to focus on their bodies, women and not men, continued to have body-related thoughts after the study was presumably over (Quinn et al 2006).…”
Section: Objectification Theory and Healthmentioning
confidence: 99%
“…Thus, although the intent in endorsing strategies like self-weighing is to promote health, an unanticipated and potentially negative consequence that may result is a harmful preoccupation with the physical self (i.e., increased body surveillance). As we previously outlined, this increased attention to the body may be problematic, as research has documented a number of negative psychological costs to appearance-focused body monitoring among women, including body psychopathology (e.g., Calogero and Thompson 2009;Melbye et al 2008;Moradi et al 2005;Tiggemann and Kuring 2004). Consequently, our goal here was to examine the possibility that body surveillance could be one mechanism through which self-weighing exerts a negative influence on body image.…”
Section: The Present Studymentioning
confidence: 99%
“…Other work has indicated that women who are less dissatisfied with their bodies reported more frequent sexual activity and were more likely to initiate sex and try new sexual behaviors than those who were less satisfied (Ackard, Kearney-Cooke, & Peterson, 2000;Schooler, Merriwether, & Caruthers, 2005;Trapnell, Meston, & Gorzalka, 1997). Women with lower body dissatisfaction are also more likely to report greater sexual confidence (La Rocque & Cioe, 2011;Weaver & Byers, 2006) and greater sexual esteem (Calogero & Thompson, 2009; see also Dove & Wiederman, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, objectification theory suggests, and empirical evidence indicates, that self-surveillance is related to discomfort in sexual situations in women (Calogero and Thompson 2009;Fredrickson and Roberts 1997). This reduces women's enjoyment of sex.…”
Section: Introductionmentioning
confidence: 99%